Associations between overweight, obesity, and mental health: a retrospective study among European adults aged 50+ - Rindler, Gregor Alexander; Gries, Anna; Freidl, Wolfgang (Frontiers in Public Health, 2023)
The comorbidities associated with overweight and obesity have been well researched and scientifically proven while their relationship to mental health is still not verified. This study is aimed at investigating reciprocal associations between obesity and mental health, and is intended to further analyze possible long-term effects using data from the Survey of Health, Ageing and Retirement in Europe (SHARE). In order to do that, waves 4 and 8, conducted in 2010 and 2019/20 of this survey, were analyzed in a cross-lagged panel approach including 16,184 adult Europeans (50+) using multiple linear regression analysis focusing on the Body Mass Index (BMI), depression status and quality of life (QoL). Findings yield significant cross-lagged effects in one direction regarding BMI predicting QoL and depression state, whereas depression state and QoL do not significantly predict BMI. Findings include people living with obesity, overweight, and underweight showing significantly decreased levels of QoL as well as increased depression scores compared to people of normal weight over a lag time of 10 years, where people living with obesity indicate the strongest effect. However, results do not confirm reciprocal associations in the long term. Hence, there is a strong need to carry out further research on this issue.